The relationship between ethical leadership, teacher motivation, and commitment in public schools in Portugal - Neves, Maria de Lurdes Gomes (Frontiers in Education, 2025)
In the current educational context, transformations are continuous, and the ethical dimension of leadership has become one of the main concerns of school cluster directors, given its direct influence on teachers’ motivation. This study, conducted with a sample of 204 teachers from public schools in Portugal, aimed to investigate the relationship between ethical leadership, motivation, and commitment. The results revealed that ethical leadership is positively correlated with intrinsic motivation and organizational commitment (OC). On the other hand, despotic leadership exhibits a negative correlation with OC and intrinsic motivation. Furthermore, it was found that commitment plays a mediating role in the effect of ethical leadership on teachers’ intrinsic motivation. These findings underscore the importance of promoting ethical leadership in schools, not only to foster teachers’ motivation but also to strengthen their commitment to the institution. Conversely, the need to avoid despotic practices is emphasized, as they can adversely affect not only teachers’ motivation but also their commitment to the educational organization. These conclusions further highlight, as future research avenues, the importance of promoting ethical leadership in educational institutions to ensure a healthy and productive work environment for teachers.